Occupation Anarchique Du Domaine Public Dans La Commune De Yopougon A Abidjan : Une Complicite Des Autorites Locales ? - Yaya, Coulibaly; EugÃ¨ne, Kra Kouadio; Amadou, Coulibaly (European Scientific Journal, ESJ, 2017)
Long perceived as an institutional response to the problem of local development, the decentralization adopted and introduced in the 1980s favored the creation of numerous communes in CÃ´te d’Ivoire. These local and regional authorities, which in principle have legal personality and financial autonomy, are struggling to satisfy the expectations of politicians and populations. Consequently, the consequences are felt in space and we are witnessing an anarchic and illegal occupation of public servitudes as is the case in the commune of Yopougon in Abidjan. The present study is thus a contribution to the lasting resolution of the problem of the anarchic occupation of the public domain for the preservation of the urban landscape of municipalities. The main objective is to show the impact on the urban landscape of the use of the improvement of municipalities’ own revenue. The methodology used to achieve this objective was based on the observation, inventory of the spaces documentary research, observation and maintenance with local and governmental authorities to obtain data on the mode of acquisition and enhancement of spaces. The results reveal that these areas are occupied with more or less the agreement of the various local and governmental authorities and their management remains problematic.